The students' satisfaction towards school facilities at tahfiz schools / Nur Alia Ishak and Suwaibatul Islamiah Abdulahsani - Ishak, Nur Alia; Abdulahsani, Suwaibatul Islamiah (2018)
School facilities have an important role in ensuring the quality of teaching and learning and to achieve a good quality in education. The aim of this research paper is to investigate students' satisfaction of school facilities specifically at tahfiz schools and to identify the school facilities affecting academic performance. This paper identified 6 major facilities components that reflect the learning environment and evaluated the effect of facilities towards students' academic performance. The distribution of 100 questionnaire survey forms for two schools was conducted to derive the findings. The data used were mean and Pearson correlation analyses. The results showed that there was a significant relationship in two variables which are school facilities and academic performance. Meanwhile, the average mean shows the overall school facilities in moderate satisfaction level. The study concludes that the head of the school and the parties involved should understand and maintain the facilities provided in order to enhance learning among students and thus achieve educational purposes.